2022
DOI: 10.1002/chem.202203259
|View full text |Cite
|
Sign up to set email alerts
|

Direct Coupling of Methane and Carbon Dioxide on Tantalum Cluster Cations

Abstract: Understanding molecular‐scale reaction mechanisms is crucial for the design of modern catalysts with industrial prospect. Through joint experimental and computational studies, we investigate the direct coupling reaction of CH4 and CO2, two abundant greenhouse gases, mediated by Ta1,4+ ions to form larger oxygenated hydrocarbons. Coherent with proposed elementary steps, we expose products of CH4 dehydrogenation [Ta1,4CH2]+ to CO2 in a ring electrode ion trap. Product analysis and reaction kinetics indicate a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…18 The reaction of methane with the mono-cations of the 5d series is highly efficient and the thermal rates are close to, or on the order of, the collision rate. 15,21,22,26,27 At low collision energies, the main product channel is a species with the formal composition [M,C,2H] + and molecular hydrogen H 2 . Thermodynamic arguments and recent spectroscopic investigations showed that the carbene M]CH 2 is the favoured isomer compared to the carbyne H-M-CH + .…”
Section: Introductionmentioning
confidence: 99%
“…18 The reaction of methane with the mono-cations of the 5d series is highly efficient and the thermal rates are close to, or on the order of, the collision rate. 15,21,22,26,27 At low collision energies, the main product channel is a species with the formal composition [M,C,2H] + and molecular hydrogen H 2 . Thermodynamic arguments and recent spectroscopic investigations showed that the carbene M]CH 2 is the favoured isomer compared to the carbyne H-M-CH + .…”
Section: Introductionmentioning
confidence: 99%